2022
DOI: 10.3390/vaccines10071125
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clinical Profile and Treatment Outcome in Vaccinated and Unvaccinated SARS-CoV-2 Infected Patients

Abstract: Vaccines against severe acute respiratory syndrome-corona virus-2 (SARS-CoV-2) infection, which causes coronavirus disease–19 (COVID-19) in humans, have been developed and are being tested for safety and efficacy. We conducted the cross-sectional prospective cohort study on 820 patients who were positive for SARS-CoV-2 and were admitted to Princess Krishnajammanni trauma care centre (PKTCC), Mysore, which was converted to a designated COVID hospital between April 2021 to July 2021. After obtaining the informed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 86 publications
5
7
0
Order By: Relevance
“…Our findings on reduced ferritin levels in vaccinated COVID‐19 patients align with the study of Korishetter et al, 22 that compared the biochemical parameters in these patients with respect to vaccination status. Ferritin is an acute phase reactant and is known to contribute to the cytokine storm in COVID‐19 23 .…”
Section: Discussionsupporting
confidence: 91%
“…Our findings on reduced ferritin levels in vaccinated COVID‐19 patients align with the study of Korishetter et al, 22 that compared the biochemical parameters in these patients with respect to vaccination status. Ferritin is an acute phase reactant and is known to contribute to the cytokine storm in COVID‐19 23 .…”
Section: Discussionsupporting
confidence: 91%
“…A good approximation can be made that vaccination dose indeed reduces the rate of post-COVID-19 conditions, but there is a more pronounced effect on certain outcomes than others, with anosmia, fatigue, abnormal taste, and pain being the most consistent. Interestingly, our study did find a weak positive association with vertigo postvaccination, similar to how some studies report more vomiting in vaccinated groups 17 . The exact pathophysiology and sequence of events in ‘long COVID’ have yet to be fully studied.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Korishettar et al . reported that the duration of hospital stay was lower in vaccinated patients (average of 5.65 days) than in unvaccinated patients (average of 9.43 days) 17 . Our study focused specifically on the duration of illness (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations